The Mandate of Art. 16.3 of Spanish Constitution to the Public Powers and the School: Beyond Instruction - Rodríguez Moya, Almudena (Estudios Eclesiásticos. Revista de investigación e información teológica y canónica, 2021)
Since the adoption of the Constitution in 1978, the «religious question» has undergone several changes. From a legal perspective, the most relevant de velopment has undoubtedly been the transition from a totalitarian, confessional state to a democratic state characterized by positive secularism. From a social perspective, and due to the new system of religious freedom, Spain has moved from being a country with a single faith to one based on religious pluralism. Article 16.3 of the Constitution mandates public authorities to take the religious beliefs of Spanish society into account. It is now time to consider to what extent this mandate affects schools.
Keywords: religious pluralism; public authorities; religious freedom; positive secularism; school